TAFSIR TABI'IN (Tokoh, Metode, Sumber dan Corak) - Asnin Syafiuddin (STAI Asy-Syukriyyah, 2015)
The interpretation of the Prophet, companions, and tabi'in grouped into one group called bi Tafsir Al-ma'tsur. When the rule of Islam has spread to new areas, raises problems that need solving of the holy book of the Qur'an. When viewed broadly interpretation performed by tabi'in, then there is no much difference with characteristic friend interpretation, the difference was only found in the inclusion elements Israiliyyat, at this time interpretation be maintained by way of history and began to appear the difference sect.